Child Mobility and Rural Vulnerability in Senegal : Climate Change and the Role of Children in Household Risk Management Strategies in Rural Senegal - World Bank (Washington, DC, 2013)
Senegal has a relatively low child mobility rate (children who leave their parents). Yet, concern has been raised with regards to the vulnerability of girls who work as domestic servants and boys who leave to study the Koran within informal structures. To learn more about their numbers and the reasons why they leave, Fafo Institute for Applied International Studies (Fafo) and l Ecole nationale d economie appliquee (ENEA), supported by the World Bank trust fund, TFESSD, in 2009, launched a rural household survey that aimed to quantify child mobility practices and identify the features of the households from which the children come. The vulnerability of rural households to risks and shocks related to climatic conditions like drought, irregular rainfall, animal disease and locust was of special concern. This report presents the main results of this project.